Academic achievement of immigrant children in Irish primary schools: the role of capitals and school context - Fran McGinnity; Aisling Murray; Merike Darmody (Eesti Haridusteaduste Ajakiri, 2022)
Educational achievement is one of the key indicators of labour market success, yet previous research shows that in many countries, children from immigrant backgrounds struggle to match their native peers in terms of achievement. Despite high educational aspirations, migrant parents may struggle to "convert" their social and cultural capital to support their children’s achievement in their country of destination. Ireland is an interesting case study as there was substantial and  rapid immigration of a diverse group of migrants, many of whom were European, to a school system that was predominantly White, Catholic, Irish and English-speaking. Drawing on the extensive literature on academic achievement of immigrant children and youth, this paper explores the academic achievement of 9-year-old immigrant children in a ‘new immigration country’, just after the peak of inward migration. The results show that unlike in many ‘old’ immigrant- receiving countries, the immigrant "penalty" in achievement in Ireland is modest, with social and cultural capital playing a salient role in English reading achievement, particularly for East Europeans, for whom the gap is greatest. Understanding the patterns of linguistic integration for recent migrant children may help us understand these processes in the case of subsequent movements of children and their families in Europe.